Decoppering of Lead and Hard Lead by Stirring with Sulfur and Pyrites - Jensen G; Segnit ER (The Australasian Institute of Mining and Metallurgy, 1980)
The decoppering of soft and hard leads was investigated by stirring in an open pot, using sulfur or sulfur plus pyrites, or sulfur plus pyrrhotite, as reagents. Lead samples taken during the process were analysed for copper. Dross samples were examined by optical micro- scope, SEM and XRD. Soft lead containing silver can be decoppered satisfactorily by stirring with 0.1% S at low temperatures - close to 330¦C. Soft lead, whether containing silver or not, can be decoppered satisfactorily at higher temperatures by stirring with 0.1% S plus 0.4% pyrites. Then CuFeS2, Cu5FeS4 and PbS are formed, instead of Cu2S, CuS and PbS when using S alone. Hard lead containing tin can be decoppered satisfactorily by stirring with 0.1% S at temperatures from 320-400¦C. When stirring with 0.1% S plus 0.4% pyrites, reversion of copper from dross to lead on prolonged stirring does not occur. Hard lead without tin can be decoppered with S plus pyrites better than with S alone, but the presence of antimony hinders the decoppering, which is less effective on lead with 5.5% Sb than with 2.3% Sb.